Short-Term Neuropsychiatric Tolerability of Bictegravir Combined with Emtricitabine/Tenofovir Alafenamide in Clinical Practice. Issue 2 (February 2020) - Hoffmann, Christian; Schewe, Knud; Fenske, Stefan; Buhk, Thomas; Sabranski, Michael; Adam, Axel; Hansen, Stefan; Stellbrink, Hans-Jürgen
Background: Neuropsychiatric AEs (NPAEs) leading to dolutegravir (DTG) discontinuation were seen more frequently in real-world use than in randomized clinical trials (RCTs). The recently approved fixed-dose combination bictegravir plus emtricitabine and tenofovir alafenamide (BIC/F/TAF) has shown comparable NPAE rates but some favourable patient-reported outcomes in RCTs compared with DTG. We were interested in its neuropsychiatric tolerability in clinical practice. Methods: All patients starting BIC/F/TAF from June 2018 in a single centre (two subcentres) were followed retrospectively. Discontinuation rates due to any AEs and NPAEs were compared with those of patients initiating DTG-based regimens. Results: As of May 2019, a total of 943 patients (852 males, 76 females, 15 transgender and gender diverse) initiated BIC/F/TAF outside RCTs. After a median follow-up of 6.2 months, 50 (5.3%) and 31 (3.3%) patients had discontinued BIC/F/TAF due to any AEs or to NPAEs, respectively. In multivariate analysis, a pre-existing depression and subcentre remained predictive for NPAEs, but not age, gender, ethnicity or prior DTG-related AEs. Compared with 1, 043 patients treated with DTG-based regimens, the estimated NPAE-related discontinuation rate with BIC/F/TAF was comparable during the first 6 months ( P =0.36). Cross-intolerance was low, and only 5/55 patients with prior DTG intolerability had to discontinue BIC/F/TAF due to NPAEs. Conclusions: Short-term tolerability of BIC/F/TAF was comparable to DTG-containing regimens. As seen with DTG, discontinuation rates were higher than in RCTs. A pre-existing depression but also physician's awareness may have an impact on tolerability and continuation of BIC/F/TAF. In contrast, prior intolerability of DTG was of limited predictive value.